FAKTOR INFORMASI ONLINE DALAM PENGAMBILANKEPUTUSAN INVESTOR PADA PLATFORM CROWDFUNDING BERBASIS DONASI - Pratama, Rendy Adhi; Sulung, Liyu Adhi Kasari; Rahayu, Sri (UI Scholars Hub, 2021)
This study aims to analyze the role of online information in the decision-making process of investors in the form of donation-based crowdfunding. We use Kitabisa.com as a donation-based crowdfunding platform and collect 74 data on donation projects. This study uses the combination of a regression model with cross section data and an Elaboration likelihood model. The results of this study found that several very important online information variables, such as updates and shares on Facebook, proved significant to influence investors' decisions on crowdfunding platforms in Indonesia. The results of this study prove that the central routes obtained from project updates made by the project owner and the peripheral route, which are obtained from the number of shares on Facebook social media, have equally significant factors in influencing the success of raising funds through the crowdfunding system in Indonesia. Therefore, the two factors, both in terms of the central route (from the updates factor) and the peripheral route (from Shares on Facebook) have an influence on the success of crowdfunding funding on the Kitabisa.com platform.